Finding the Wanderer Nerve: A Novel Use of ETT Surface Electrodes in Vagal Nerve Stimulator Insertion Surgery - Prasad, Sethulakshmi; Varma, Salini; Sethuraman, Manikandan (Journal of Neuroanaesthesiology and Critical Care, 2023)
Endotracheal tube (ETT) surface electrodes have been in vogue for vagal nerve identification and monitoring for a while. They have been used in thyroid surgeries as well as neurosurgical procedures involving the skull base or brain stem. These electrodes have been proved vital in preventing inadvertent vagal nerve injury and damage during such procedures. However, ETT surface electrodes have not yet been used in vagal nerve stimulator insertion surgeries. Here, we report the first such case of vagal nerve stimulator insertion surgery wherein ETT surface electrodes were successfully used for vagal nerve identification.
Keywords: vagus nerve; endotracheal tube surface electrodes; neuromonitoring; vagal nerve stimulation